NEW MODEL OF SHARIA BANKING STRATEGY IN INDONESIA: KPPS ONLINE REPORT - Indra Gunawan, Cakti (International Research & Development for Human Beings (IRDH), 2025)
Indonesia, as one of the largest country in Asia, plays an important role in the development of the Asian economy and economic rotation. With a dense population and a country that has very promising economic potential, Indonesia has become one popular country in economic competition in Asian countries. An effort to improve the economy of a country, it is necessary to have financial institutions that can focus on managing the country's economic sector.